Klaim Berlebihan dan Influencer: Daya Tarik Pembelian Impulsif Produk Skincare - Mahnun Masadi (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This study aims to examine the influence of excessive claims on skincare products and the role of influencers on consumer impulsive buying, as well as examine the mediating role of product attractiveness in these relationships. The research method used a survey with a sample of 100 respondents who filled out a questionnaire based on the Likert scale. Data were analyzed through validity, reliability, multiple linear regression, and mediation analysis tests using bootstrap techniques. The results show that excessive claims and influencer influence contribute positively and significantly to impulsive buying. In addition, product appeal has been shown to mediate the relationship between over-claims and impulsive buying, as well as between influencers and partial impulsive buying. In conclusion, marketing strategies that involve product claims and influencers can increase impulsive buying through increased product appeal. This research provides important implications for the development of skincare product marketing strategies to be more effective and attractive to consumers. The hypothesis test yielded an F-value of 79.459 with a p-value of 0.000. Since the p-value is less than 0.05, the regression model as a whole is statistically significant in explaining the dependent variable Total Y. This indicates that the predictors, TOTALX2Z and TOTALX1Z, together have a significant influence on Total Y."